Exploring halogen⋯halogen interactions in supramolecular self-assemblies of BODIPY networks. Issue 31 (21st July 2022) - Topaloğlu Aksoy, Burcu; Dedeoglu, Burcu; Zorlu, Yunus; Ayhan, Mehmet Menaf; Çoşut, Bünyemin
Abstract : In this study, the efficiency of halogen⋯halogen interactions to control supramolecular assemblies of boron dipyrromethene (BODIPY) (B1–B5 ) derivatives was explored. Abstract : In this study, the efficiency of halogen⋯halogen interactions to control supramolecular assemblies of boron dipyrromethene (BODIPY) (B1–B5 ) derivatives was explored. BODIPY scaffolds were systematically decorated with iodine groups to promote halogen⋯halogen interactions. Single crystal X-ray diffraction analysis revealed the formation of XB interactions, I⋯I and I⋯F contacts, which led to impressive halogen-bonded supramolecular tubular-like (B1 ), domino-like (B2 ), 1D linear chain (B3 ), helical (B4 ), and 1D linear chain (B5 ) self-assemblies. The molecular electrostatic potential (MEP) showed the presence of σ holes on the outer tip of the iodine groups for all compounds and the positive potential increases with each additional iodine substitution on the BODIPY scaffold. Symmetry-adapted perturbation theory (SAPT) analysis showed that the dispersion and electrostatic components are the major source for all XB formations. The additional AIM theory analysis showed the bond critical points (BCPs) between I⋯I, F confirming the formation of halogen bonds in these assemblies.